1994
DOI: 10.1103/physrevlett.73.1935
|View full text |Cite
|
Sign up to set email alerts
|

An On-Line Laser Ion Source Based on Resonance Photoionization in a Gas Cell

Abstract: First results obtained with a new type of on-line laser ion source based on resonant photoionization in a buffer gas cell are presented. The main advantages of this new target-ion-source system are its high efficiency, its selectivity, its short delay time, and its universality. This is demonstrated with the production of an isotopically and isobarically pure beam of "Ni (T~/2 = 200 ms).PACS numbers: 29.25.NiAlready during the first conference on nuclei far from stability dealing with the question "Why and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 19 publications
(8 reference statements)
0
29
0
Order By: Relevance
“…The rf-sextupole has the advantage of a higher overall mass resolution and better transmission efficiency. A laser ion source has also recently been developed [11] based upon resonance ionisation in a gas cell [12,13] and variations thereof [14]. Developments in ion guide technology [8] have shown that the addition of inguide electric fields improves the extraction efficiency and reduces the evacuation time of radioactive ions.…”
Section: -2351mentioning
confidence: 99%
“…The rf-sextupole has the advantage of a higher overall mass resolution and better transmission efficiency. A laser ion source has also recently been developed [11] based upon resonance ionisation in a gas cell [12,13] and variations thereof [14]. Developments in ion guide technology [8] have shown that the addition of inguide electric fields improves the extraction efficiency and reduces the evacuation time of radioactive ions.…”
Section: -2351mentioning
confidence: 99%
“…This method has been proposed in 1992 [4] and subsequently intensively studied (first at LISOL) and developed [5][6][7][8][9][10][11][12][13]. Known as In-Gas Laser Ionization and Spectroscopy (IGLIS), it is based on stopping of nuclear reaction products in a gas cell and subsequent selective resonance laser ionization [5][6][7][8][9][10][11][12][13].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[1]. In recent years, diverse attempts have been started to improve the intensities of refractory elements at mass separators, such as the use of He-jet systems after nuclear reactions [2] or the development of on-line laser ion sources [3]. However, the intensities as obtained until now are still relatively small.…”
Section: Measurements Of the Electric Quadrupole Moment Of Nb And Zr mentioning
confidence: 99%